The Integration of Education Eobotics in High School in the Light of the BNCC: Potentialities and Challenges – Experience Report - Lima, João P. R. De; M. Filho, Elson A. U.; Costa, Fabio A. S.; Rossiter, Sarah T. De S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This work is an experience report on the integration of educational robotics into the school curriculum, highlighting the importance of adapting education to rapid technological advances. The inclusion of robotics in classes, using the Arduino platform, meets the competencies of the National Common Curriculum Base (BNCC), such as digital culture and computational thinking. Results obtained from the project implementation show that students improved their problem-solving skills and became more engaged in learning. Practical activities promoted an interactive learning environment, fostering creativity and collaboration. The study reports on the implementation of practical classes in a private school in City X, where students develop real projects, promoting playful and continuous learning. The activities are carried out weekly using a dynamic laboratory that stimulates interaction and creativity, preparing students for the digital future.